Pengaruh Intellectual Capital dan Financial Literacy terhadap Financial Well-Being dengan Financial Distress sebagai Variabel Mediasi - Dian Sonya Kristanti; M. Sodik; Dharmayanti Pri Handini (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The culinary sector of Micro, Small, and Medium Enterprises (MSMEs) plays a crucial role in supporting the economy, but they still face financial management challenges such as mixing personal and business funds, weak planning, and poor bookkeeping. These conditions are prone to triggering Financial Distress, which impacts the Financial Well-Being of business owners. This quantitative explanatory research aims to analyze the influence of Intellectual Capital and Financial Literacy on Financial Well-Being, with Financial Distress as a mediating variable, in the culinary MSME Baking Lovers Lawang (BLL) Community in Malang Regency. The research population included 545 MSMEs, with a sample of 85 respondents determined using the Slovin formula (10% error tolerance) and proportional random sampling techniques. Data collection utilized a five-point Likert scale questionnaire distributed via Google Form, supported by secondary data from related literature. Data analysis used SPSS for descriptive statistics and SmartPLS 4 with the SEM-PLS method, including evaluation of the outer model, inner model, and bootstrapping procedures. The results of the investigation proved that Intellectual Capital and Financial Literacy had a significant positive effect on Financial Well-Being, but a significant negative impact on Financial Distress. On the other hand, Financial Distress has a significant negative effect on Financial Well-Being and is proven to mediate the relationship between the two independent variables.